2020
DOI: 10.3390/agriculture10090410
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining the Adoption of Strategies Used by Smallholder Farmers to Cope with Climate Variability in the Eastern Free State, South Africa

Abstract: This study was undertaken to understand the smallholder farmer’s perception of the effects of climate variability, their adaptation strategies to cope with climate variability and factors determining the adoption of their adaptation strategies in the eastern Free State Province of South Africa. Adaptation strategies were grouped into two categories, i.e., traditional adaptation strategies and scientific adaptation strategies. Traditional adaptation strategies consisted of practices that require minimal technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Similarly, 81% and 78.1% of rice farmers have perceived late commencement and early cessation of rain Unpredictable rainfall pattern and distribution was cited by more than 83 percent of rice farmers as one of the climate change threats affecting rice output in the area. Farmers find it extremely difficult to plan their farming operations due to the unpredictable rainfall pattern and distribution, as they are frequently stuck (confused) on how to go about their rice cultivation [61,62]. Rainfall unpredictability is a major climate change event affecting agriculture [54,62,63].…”
Section: Farmers' Perception Of Climate Eventsmentioning
confidence: 99%
“…Similarly, 81% and 78.1% of rice farmers have perceived late commencement and early cessation of rain Unpredictable rainfall pattern and distribution was cited by more than 83 percent of rice farmers as one of the climate change threats affecting rice output in the area. Farmers find it extremely difficult to plan their farming operations due to the unpredictable rainfall pattern and distribution, as they are frequently stuck (confused) on how to go about their rice cultivation [61,62]. Rainfall unpredictability is a major climate change event affecting agriculture [54,62,63].…”
Section: Farmers' Perception Of Climate Eventsmentioning
confidence: 99%
“…The South African government has made efforts to support and subsidize smallholder farmers to increase productivity [8]. However, due to technical inefficiencies among smallholder farmers, there is still substantial productivity gap between the maximum achievable yield and definite levels of production [9,10]. As a result, smallholder farmers are unable to reconcile and balance their incurred costs and retain profits.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, existing literature has indicated that traditional methods have become ineffective for coping with the medium and long-term impacts of climate change [12]. Its use has been associated with the overexploitation of natural resources, increasing pressure on water reservoirs, creating pollution problems, consuming time and money, and low yields due to crop damage caused by over or under irrigation [22][23][24]. Therefore, this has triggered much discussion of converting to more improved agricultural technologies such as climate-smart irrigation technologies (CSIT) [21].…”
Section: Introductionmentioning
confidence: 99%